Para uma história da análise do comportamento no Maranhão - Moreira, Juliana Benigno (2011)
Behavior analysis is a science that has been concern with its narrative and the examination of its own history. In Brazil, this narrative is focused on those states where behavior analysis was first been implemented, such as São Paulo and the Federal District (Brasília). However, with its expansion throughout the country, it is also important to learn about its dissemination in other states. This paper will focus on the behavior science expansion and history in Brazil, featuring its growth in a state in which its implementation has not been studied nor has been explored: Maranhão. The goals of this paper is: characterize the beginning of the behavior‟s analysis in Maranhão state, investigating it‟s insertion in the curriculum of psychology courses of the State and the insertion of analysis‟s teachers in those courses; describe the academic achievements and professional experience in behavior analysis of the teachers; and describe the student knowledge about behavior analysis. In order to collect the necessary information interviews were performed with all the behavior analyzes teachers in the three high education institutions located in Maranhão. Also, information was acquired from the psychology department administration offices and from their website. All three institutions had behavior analysis classes starting when psychology major was implemented; however not all the institutions had teachers with behavior analysis background teaching the discipline. The first faculty with academic credentials on behavior analyzes at the Federal University of Maranhão (UFMA) was hire 10 years after the psychology major had been in place. Conversely, the other two higher education institutions, Faculdade Pitágoras and Centro de Ensino Unificado do Maranhão (UniCEUMA), always had teachers with strong behavior analysis background. Currently all the teachers responsible for the behaviors analysis lectures have well-built academic credentials, that include master and/or PhD in this area. All the teachers has master degree in behavior analysis and those who have PhD also do or didi it, in this area. This paper also shows that behavior analysis‟s teachers, beside lectures, are responsible for student supervision, overseen internalships, research project, and some chair their respective department. The behavior analysis curriculum used in the different institutions demonstrate there are not a homogenous instruction of this discipline in Maranhão: UFMA offers three introduction classes for behavior analysis, two techniques and theory of psychoanalysis (TTP) classes, and internalships with emphases in school behavior and clinical behavior. UniCEUMA has one basic experimental psychology class, one TTP, and one behavior internalship with clinical emphases. Faculdade Pitágoras offers Experimental Analysis of Behavior, Laboratory Practices in Experimental Analysis of Behavior and Elements of the Cognition-Behavior Approach